(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Ikat, a renowned fabric art form, epitomizes the intricate relationship between weaving techniques and artistic expression. The term "ikat" originates from the Malay-Indonesian word meaning "to bind," reflecting the tie-dye processes used to pattern the yarn before weaving. Interlacements—where warp and weft threads interact in predetermined sequences—play a pivotal role in ikat’s aesthetic, lending these textiles their distinct charm. This article delves into the artistic, cultural, and technical dimensions of interlacements in ikat fabrics, highlighting their significance in maintaining the legacy and innovation of textile design.